2017
DOI: 10.1128/mbio.02129-16
|View full text |Cite
|
Sign up to set email alerts
|

Viruses in the Oceanic Basement

Abstract: Microbial life has been detected well into the igneous crust of the seafloor (i.e., the oceanic basement), but there have been no reports confirming the presence of viruses in this habitat. To detect and characterize an ocean basement virome, geothermally heated fluid samples (ca. 60 to 65°C) were collected from 117 to 292 m deep into the ocean basement using seafloor observatories installed in two boreholes (Integrated Ocean Drilling Program [IODP] U1362A and U1362B) drilled in the eastern sediment-covered fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 71 publications
(100 reference statements)
2
70
0
4
Order By: Relevance
“…Nitrosopumilus) but also to viral‐related genes, including predicted major capsid proteins (MCP), portal proteins, tail tape measure proteins and the large subunit of viral terminases. Both the terminase and the MCP proteins gave hits with low identity (32–35%) to a complete, unclassified archaeal virus (KY229235) recovered from a metagenomic assembly of a sample ~550 m below the seafloor (Nigro et al, ). Like in the case of KY229235, our contig had identical repeated sequences (>30 nucleotides) at the 5′ and 3′ terminal regions suggesting a complete viral genome.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrosopumilus) but also to viral‐related genes, including predicted major capsid proteins (MCP), portal proteins, tail tape measure proteins and the large subunit of viral terminases. Both the terminase and the MCP proteins gave hits with low identity (32–35%) to a complete, unclassified archaeal virus (KY229235) recovered from a metagenomic assembly of a sample ~550 m below the seafloor (Nigro et al, ). Like in the case of KY229235, our contig had identical repeated sequences (>30 nucleotides) at the 5′ and 3′ terminal regions suggesting a complete viral genome.…”
Section: Resultsmentioning
confidence: 99%
“…V iruses infect all known forms of life and are the most abundant and diverse biological entities of all Earth's ecosystems, including extreme environments such as the oceanic basement (1). Viruses play an integral role in the life cycle of their hosts, affecting not only their population demography but also their genetic diversity, thus strongly influencing the function, ecology, and evolution of complete communities and ecosystems (2).…”
Section: Abstract Bacteriophages Shotgun Metagenomics Virusesmentioning
confidence: 99%
“…Metagenomic studies of the oceans (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and other environments (15)(16)(17)(18)(19) have shown that viruses indeed are diverse and abundant in most habitats. Viruses have been found even below the basaltic basement (1), where most of them were related to Archaea and were hard to classify. This reflects a constant technical caveat in all viromic studies, since databases are incomplete and a large number of reads remains uncharacterized and are referred to as "dark matter," correlating with the "dark biodiversity" of their hosts (20).…”
Section: Abstract Bacteriophages Shotgun Metagenomics Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being included in the database (Figure 1B), sequences annotated to MAGs and SAGs from inhabitants of crustal subsurface habitats such as ammonia oxidixing Thaumarchaeota, Bathyarchaeota, sulfide oxidizing Epsilonproteobacteria, and iron oxidizing Zetaproteobacteria 4,5,12 are notably missing in the gene expression dataset of Li et al 1 (Figure 1B). While all subsurface gene expression data are prone to contamination due to the low biomass as an unavoidable challenge, it is nevertheless expected in the case of truly active subsurface microbial communities that at least some sequences derived the typical inhabitants of these extreme environments should be represented with reliable levels of sequencing coverage.…”
Section: Main Textmentioning
confidence: 99%